Solar installation occupational risks: A systematic review. (April 2023) - Duroha, Jesse C.; Macht, Gretchen A.
Highlights: Solar industry is experiencing notable growth in response to renewable energy demand. There is limited knowledge and data understanding the risks to solar installers. 365 articles were selected via systematic literature review and screened to 31 papers. Emerging areas are heat stress, manual handling, and musculoskeletal disorders. Future ergonomic studies are vital to measure and mitigate risks in PV installations. Abstract: The adoption of solar photovoltaic (PV) technology and infrastructure are increasing rapidly to meet the ever-growing global need for renewable energy sources. An obstacle to solar PV growth is the severity of the occupational safety risks associated with their installation. Although PV installers are known to experience some of the most significant and widespread construction-related occupational safety risks, PV installer accident investigation research, reporting, and verification are limited. To contribute to this literature gap, this paper conducts a systematic literature review to understand and present the occupational safety risks, mitigation measures, and current and potential safety research areas associated with PV installations. A systematic literature search for relevant articles was conducted from October 2021 to January 2022 using the Scopus, Web of Science, Science Direct, and PubMed databases identifying 365 articles by their title. After screening these articles with various selection criteria, 31 articles were selected as relevant to the research questions of this study. These selected articles identified electrical and fire risks, heat stress, manual handling risks, and fall risks as the major occupational safety risk categories associated with PV installations. This study can aid solar installation companies, occupational safety professionals, and policymakers in gaining a deeper understanding of the safety risks and mitigation measures associated with PV installations as they develop protocols and guidelines to safely support the solar workforce's development.